Virtual congkak - Darayani, Musa (2018)
Virtual Congkak is a mobile game that implement the technology of Augmented Reality (AR). AR is the ability to display the computer generated display to enhance user’s real world experience. Congkak is a traditional game which been played since a long time ago. A Congkak board and some Congkak stone which usually using marbles are needed as the game equipment. In this days of advance mobile game technology, there are modern games that use violence theme. This will make people forget about traditional games that actually gives more aesthetic and good value. There are some existing Congkak game but there is not yet a traditional game that implies the Augmented Reality Technology. In the real world of a player, Congkak games needs a wooden board to play so it cannot be access anywhere. Since Virtual Congkak is a mobile based game, it is portable and can be played anywhere at any time. User only needs a smartphone, the Virtual Congkak application and marker to play the game. The Virtual Congkak will display when user points to the AR Marker by using their mobile phone’s camera as the extension. The Object model of This application is developed by using 3D Builder software by Windows and the gameplay is developed by using the Unity Software to compile all the 3D Objects into one running application by implementing the code which is the C# code. Before this system were develop, information about the rules of playing the Congkak is searched and developed into a set of pseudocode. The Virtual Congkak is aimed to gives user the aesthetic values of Traditional games.